Investigation of Pre-Service Science Teachers’ Sustainable Consumption Behaviors in Terms of Some Variables - Keleş, Özgül (European Journal of Sustainable Development, 2017)
The purpose of the current study is to investigate pre-service science teachers’ sustainable consumption behaviors and the factors affecting them in terms of some variables (gender and grade level). The study group of the current research is comprised of 154 pre-service teachers attending the Department of Science Education in the Faculty of Education of Aksaray University. The study employed the descriptive survey method, one of the qualitative research methods. As the data collection tool, “The Sustainable Consumption Behavior Scale” developed by Do?an, Bulut and Ç?mr?n (2015) was used in the study. The Cronbach alpha reliability of the scale was calculated to be ?=.77. In the statistical analysis of the data, SPSS was used. In the analysis of the data, Independent Samples t-Test and One Way ANOVA were run. The analysis results revealed that sustainable consumption behavior frequency of the pre-service teachers is at the medium level. It was also found that the sustainable consumption behavior scores of the pre-service teachers do not vary significantly by gender; yet, they were found to be varying significantly depending on the grade level variable. The findings of the current study may help future researchers determine other factors that affect sustainable purchasing behaviors on larger samples. Keywords: Sustainable consumer behavior, pre-service science teachers, gender, grade level